The Effect of Teacher Scaffolding and Peer-Scaffolding on Reading Comprehension and Vocabulary Ability - Herdiana; Sirojul Munir (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This study aims to analyze the effect of teacher and peer scaffolding on students' reading comprehension and vocabulary mastery based on a sociocultural perspective. The quasi-experimental research method was used in this study and involved 300 high school students. Participants were divided into an experimental group (the group that received the teacher scaffold and the peer scaffold) and a control group that received the traditional intervention. The pretest was conducted to find out their initial vocabulary skills and reading comprehension skills and ended with a posttest. Descriptive statistical analysis and one-way ANOVA analysis were used to analyze the research data. The findings of the study indicated that the experimental group that received the intervention of the teacher scaffold and the peer scaffold experienced more significant improvements in reading comprehension and vocabulary skills than the control group. The experimental group with the peer scaffolding intervention showed better ability improvement compared to the experimental group that received the teacher scaffolding intervention. This study has implications that peer scaffolding can be used to support the effectiveness of teaching reading.